Xanthomonas campestris RpfB is a fatty Acyl‐CoA ligase required to counteract the thioesterase activity of the RpfF diffusible signal factor (DSF) synthase. Issue 2 (18th June 2014) - Bi, Hongkai; Yu, Yonghong; Dong, Huijuan; Wang, Haihong; Cronan, John E.
Summary In Xanthomonas campestris pv. campestris (Xcc), the proteins encoded by the rpf (regulator of pathogenicity factor) gene cluster produce and sense a fatty acid signal molecule called diffusible signalling factor (DSF, 2(Z)‐11‐methyldodecenoic acid). RpfB was reported to be involved in DSF processing and was predicted to encode an acyl‐CoA ligase. We report that RpfB activates a wide range of fatty acids to their CoA esters in vitro. Moreover, RpfB can functionally replace the paradigm bacterial acyl‐CoA ligase, Escherichia coli FadD, in the E. coli ß‐oxidation pathway and deletion of RpfB from the Xcc genome results in a strain unable to utilize fatty acids as carbon sources. An essential RpfB function in the pathogenicity factor pathway was demonstrated by the properties of a strain deleted for both the rpfB and rpfC genes. The ΔrpfB ΔrpfC strain grew poorly and lysed upon entering stationary phase. Deletion of rpfF, the gene encoding the DSF synthetic enzyme, restored normal growth to this strain. RpfF is a dual function enzyme that synthesizes DSF by dehydration of a 3‐hydroxyacyl‐acyl carrier protein (ACP) fatty acid synthetic intermediate and also cleaves the thioester bond linking DSF to ACP. However, the RpfF thioesterase activity is of broad specificity and upon elimination of its RpfC inhibitor RpfF attains maximal activity and its thioesterase activity proceeds to block membrane lipid synthesis by cleavage of acyl‐ACP intermediates. This resulted in release of the nascent acyl chains to the medium as free fatty acids. This lack of acyl chains for phospholipid synthesis results in cell lysis unless RpfB is present to counteract the RpfF thioesterase activity by catalysing uptake and activation of the free fatty acids to give acyl‐CoAs that can be utilized to restore membrane lipid synthesis. Heterologous expression of a different fatty acid activating enzyme, the Vibrio harveyi acyl‐ACP synthetase, replaced RpfB in counteracting the effects of high level RpfF thioesterase activity indicating that the essential role of RpfB is uptake and activation of free fatty acids.